A novel method for determining the difficulty of colonoscopic polypectomy. Issue 4 (1st June 2013) - Gupta, S; Miskovic, D; Bhandari, P; Dolwani, S; McKaig, B; Pullan, R; Rembacken, B; Riley, S; Rutter, M D; Suzuki, N; Tsiamoulos, Z; Valori, R; et al.
Abstract : Introduction: Endoscopists are now expected to perform polypectomy routinely. Colonic polypectomy varies in difficulty, depending on polyp morphology, size, location and access. The measurement of the degree of difficulty of polypectomy, based on polyp characteristics, has not previously been described. Objective: To define the level of difficulty of polypectomy. Methods: Consensus by nine endoscopists regarding parameters that determine the complexity of a polyp was achieved through the Delphi method. The endoscopists then assigned a polyp complexity level to each possible combination of parameters. A scoring system to measure the difficulty level of a polyp was developed and validated by two different expert endoscopists. Results: Through two Delphi rounds, four factors for determining the complexity of a polypectomy were identified: size (S), morphology (M), site (S) and access (A). A scoring system was established, based on size (1–9 points), morphology (1–3 points), site (1–2 points) and access (1–3 points). Four polyp levels (with increasing level of complexity) were identified based on the range of scores obtained: level I (4–5), level II (6–9), level III (10–12) and level IV (>12). There was a high degree of interrater reliability for the polyp scores (interclass correlation coefficient of 0.93) and levels (κ=0.888). Conclusions: The scoring system is feasible and reliable. Defining polyp complexity levels may be useful for planning training, competency assessment and certification in colonoscopic polypectomy. This may allow for more efficient service delivery and referral pathways.